2009
DOI: 10.1007/s00775-009-0589-2
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of exogenous anion exchange in FeFbpA–NTA: significance of periplasmic anion lability and anion binding activity of ferric binding protein A

Abstract: The bacterial transferrin ferric binding protein A (FbpA) requires an exogenous anion to facilitate iron sequestration, and subsequently to shuttle the metal across the periplasm to the cytoplasmic membrane. In the diverse conditions of the periplasm, numerous anions are known to be present. Prior in vitro experiments have demonstrated the ability of multiple anions to fulfill the synergistic iron-binding requirement, and the identity of the bound anion has been shown to modulate important physicochemical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In strict contrast to holo-FbpA, phosphate is only weakly bound to apo-FbpA with a K d value of 2.3±0.3 mM at the assumed pH of 6.5 of the periplasm [12]. However, a linear correlation between anion dissociation constants in apo-FbpA and anion exchange rates in holo-FbpA prevailing over three orders of magnitude suggests similar molecular level processes for both events [22].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In strict contrast to holo-FbpA, phosphate is only weakly bound to apo-FbpA with a K d value of 2.3±0.3 mM at the assumed pH of 6.5 of the periplasm [12]. However, a linear correlation between anion dissociation constants in apo-FbpA and anion exchange rates in holo-FbpA prevailing over three orders of magnitude suggests similar molecular level processes for both events [22].…”
Section: Introductionmentioning
confidence: 95%
“…12 However, a linear relationship between anion dissociation constants in apo-FbpA and anion exchange rates in holo-FbpA prevailing over 3 orders of magnitude suggests similar molecular level processes for both events. 21 In this study, we investigate in detail the interactions between the protein and the anion in the absence of iron using extensive molecular dynamics (MD) simulations. Since the role of phosphate as a synergistic anion is much debated, we inquire the scenario that the rich environmental conditions of the periplasmic space, with its wide distribution of ionic species maintaining a 30 mV Donnan potential 22 and its gel-like properties harboring microenvironments reserved for specific tasks, 23 may be utilized to optimize the binding kinetics of FbpA.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has been shown that FbpA has a high binding affinity for Fe 3þ (K a =10 18 M -1 ) in the presence of phosphate, and that concomitant exogenous anion binding is requisite (16). Many anions complement tight iron binding, including phosphate, arsenate, oxalate, nitrilotriacetate (NTA), sulfate, and citrate, and anion exchange is facile (17)(18)(19)(20)(21). The kinetics of both iron loading and iron release are paramount to the function of FbpA in shuttling iron across the periplasm between two membranebound receptor proteins.…”
mentioning
confidence: 99%
“…The native protein binds to one Fe 3+ positively via two Tyr, one His and one Glu residues, and one phosphate as the synergistic anion, with the binding affinity up to 10 18 M À1 , and varies due to the different bound synergetic anions. [17][18][19][20][21] It is also known that the anion plays a vital role in iron binding and release, which has been verified by a series of biochemical and kinetic studies. The synergistic anion has been shown to preorganize the binding site prior to iron insertion for FbpA, 51 and to control the release of iron, because proton-assisted release of the phosphate anion is the preliminary step in iron release.…”
Section: Discussionmentioning
confidence: 88%
“…12 In addition to phosphate, a number of different exogenous anions including sulfate, oxalate, citrate and carbonate can also be utilized to facilitate the binding of Fe 3+ to FbpA. [19][20][21][22] Recently biochemical and X-ray crystallography studies by our group and others revealed that other metal ions including Hf 4+ , Zr 4+ and Ti 4+ as well as Fe 3+ when binding to FbpA, can assemble into the iron binding cleft by means of the oxo-metal clusters that could function with the known two-tyrosine motif (Tyr195 and Tyr196) as ligands, and the proteins were in an open conformation. [23][24][25][26][27][28][29][30] Therefore, it is premised that the binding of these Fe 3+ -like metal ions could either block iron binding to FbpA directly when competing with Fe 3+ , or alter the protein conformation to impede iron transport into the cytoplasmic membrane indirectly.…”
Section: Introductionmentioning
confidence: 99%